A Detour Task in Four Species of Fishes - Sovrano, Valeria Anna; Baratti, Greta; Potrich, Davide (Frontiers in Psychology, 2018)
Four species of fish (Danio rerio, Xenotoca eiseni, Carassius auratus and Pterophyllum scalare) were tested in a detour task requiring them to temporarily abandon the view of the goal-object (a group of conspecifics) to circumvent an obstacle. Fishes were placed in the middle of a corridor, at the end of which there was an opaque wall with a small window through which the goal was visible. Midline along the corridor two symmetrical apertures allowed animals to access two compartments for each aperture. After passing the aperture, fishes showed searching behavior in the two correct compartments close to the goal, appearing able to localize it, although they had to temporarily move away from the object's view. Here we provide the first evidence that fishes can solve such a detour task and therefore seem able to represent the “permanence in existence” of objects, which continue to exist even if they are not momentarily visible.